Squeezed MHD tangent hyperbolic fluid flow across a sensor surface. Issue 6 (22nd April 2022) - Sagheer, M.; Atif, S. M.; Hussain, S.; Rehman, H.
Abstract: In the present numerical study, the combined effect of temperature‐dependent thermal conductivity, linear thermal radiation, and magnetic effect on shear‐thinning tangent hyperbolic fluid past a sensor surface has been studied. After converting the modelled partial differential equations into ordinary differential equations by using similarity transformation, the system of equations is tackled with the aid of the shooting method. The influence of important parameters on the fluid motion and energy distribution is displayed graphically and analyzed in detail. The presented simulations depict that a significant rise in fluid velocity is noticed for an enhancement in the magnetic parameter while an opposite trend is observed for the temperature distribution. Moreover, the skin friction coefficient decreases as the squeezed flow index is increased.